Polar bear pirates and their quest to engage the sleepwalkers : motivate everyday people to deliver extraordinary results - Webster, Adrian, 1958- (Ascent Audio, 2023)
Polar Bear Pirates are highly focused, successful characters; they can't help but motivate everyone around them, and just like you, they love to have some fun. In their latest quest, they take on the Sleepwalkers, the workplace zombies who are with you in body but never take a step beyond the ordinary because their minds have drifted into sleep mode. Going through the motions, thinking the same old stuff, and delivering the same results, they stand out like beacons of disappointment. Sleepwalkers can be found orbiting Planet Complacency. It is a huge planet-more powerful than the inhospitable Rock Bottom, it appears to be a comfortable, safe, and popular place to be. Yet this silent assassin is responsible for snuffing out millions of dreams and kidnapping untold potential. The Polar Bear Pirates' mission is to reawaken dormant talent and release untapped potential. Join them and meet a cast of amazing characters, from Neg Ferrets and Bloaters, to Amps and Vamps. One thing's for sure, you'll come out the other side inspired and ready to get the best out of your team and the people around you. Polar Bear Pirates shows you how to motivate everyday people to deliver extraordinary results.